Impacto del impuesto a la renta único del banano en las exportaciones en la provincia de El Oro. - Cruz Solano, Martin Vicent (2018)
The only tax on income of 2% is a tax that is only taxed only on the cultivation and production of bananas in order to simplify the payment of income tax and thus be able to benefit the banana sector. According to (Cardona, Agudelo Henao, & Lopez Ramirez, 2007), taxpayers in most cases are led to increase levels of evasion, thus decreasing compliance with tax evasion by complying with various strategies to reduce evasion. According to (Palma, 2010), rent is an element of the price of goods and is not part of a regulatory price and does not cause any consequence of the price. (Ulloa & Villacre Rojas, Diagnostic of the Ecuadorian Banana Export Logistics Chain to the United States of America, 2014), the Ecuadorian banana had its origins in 1910, but in 1948 it was originated by the banana boom considered the point Starting, during the government of President Galo Plaza, in order to facilitate export promotion, the creation of credits and built bridges, roads and ports helping the transfer of the fruit to different destinations abroad. In 1952, Ecuador was considered the first banana exporting country in the world during that decade. Only three exporters controlled 80% of the banana production locally and in the 60s production grew at a giant pace. The first supplier country worldwide. According to (Olaya, Carvajal, Velasquez Restrepo, & Lopez Fernandez, 2015), financial indicators are such a useful tool at the moment of decision making and in this way to be able to strengthen the actions that generate the positive impacts with their respective corrective, It is necessary for companies to evaluate financial indicators without leaving aside financial management as it is a main objective to maximize the wealth of the companies' shareholder. (Herrera & Morelos Gómez, 2012), companies must create measures that allow to be efficient and competitive from the economic perspective, to be able to economically and financially so they can make their resources better to obtain greater productivity with results with lower costs, reason why indicates the need to carry out a thorough analysis of the economic and financial situation for the activity carried out. According to (the, 2014), in any activity the risk is an uncertain situation that every physical and legal person is exposed. In the financial field it is very important to know what is going to be presented in the future to make the best possible decision. The reason for this investigation is a study of criteria that affect the financial administration and can allow the sustainable development of the entity of the study. The objective of the research work is to focus on Mr. Quezada Alvarado Segundo del Pilar's company on the impact that the single tax on bananas and the liquidity generated by this company may have caused. For this, a methodology was used in an explanatory and descriptive way. The results that the company reflects through the financial indicators of liquidity, management, indebtedness and profitability indicate that it is at a critical point generating a concern in the business world.